Role of Both Protein C and Antithrombin III as Predictors of Stage of Liver Disease in Chronic Viral Hepatitis B or C Infected Patients - Abo-Elenein, Amany M.; Mabrouk, Maaly M.; Abou-Saif, Sabry; Saeed, Ola M.; Khodeir, Samy; Elkadeem, Mahmoud; Elashry, Heba; Haydara, Tamer; Zaghloul, Mariam S.; Seleem, Waseem M.; Elshweikh, Samah A.; Abd-Elsalam, Sherief (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background & Aims: Chronic liver disease is characterized by complex hemostatic disorders because the liver is the site where most of the coagulation factors and their inhibitors are synthesized. The aim of this study was the evaluation of protein C and antithrombin III in different stages of chronic hepatitis B and C and to determine their possible role as markers of liver cell damage in different clinical stages. Methods: The study included 60 subjects who were subdivided into 4 groups: (Group I): 15 patients diagnosed as chronic viral hepatitis B or C, (Group II): 15 patients with compensated liver cirrhosis, (Group III): 15 patients with decompensated liver cirrhosis, and (Group IV) (control group): 15 healthy individuals. History taking, clinical examination and abdominal ultrasonography were made for all subjects. Investigations were done in the form of liver function tests (ALT, AST, ALP, serum bilirubin, and serum albumin), PT, PTT, CBC. Plasma levels of Antithrombin III & protein C were estimated by automated Stago compact coagulation analyzer. Results: In all patient groups, the mean value of Protein C showed significant decrease when compared to control group, mean value of antithrombin III showed a significant decrease in compensated and decompensated subjects when compared to chronic hepatitis and control groups. Antithrombin III and protein C showed a significant negative correlation with (ALT, AST, PT, PTT, INR). However, this correlation was positive with Albumin. Conclusion: Antithrombin III and protein C are natural anticoagulants and can be considered as markers of different stages of chronic liver disease. This is supported further by the comparison between the levels of these parameters and clinical stages of liver disease. Protein C is more sensitive than ATIII as a marker of hepatocellular damage.
Keywords: protein C